Control and management of gynecological cancer in Peru - Castillo, MH (2023)
Peru, in South America, is a developing country according to the United Nations, with a population of 33.6 million inhabitants and a rugged geography. Administration of health services is often limited for the population residing in remote places. Lima, the capital city, has 9.6 million inhabitants, and therefore two thirds of the population live in the provinces.